KORELASI LAMA MENDERITA DIABETES MELITUS TIPE 2 DENGAN GANGGUAN FUNGSI KOGNITIF - , Asri Damayanti ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cognitive Dysfunction common in diabetes mellitus result from microvaskuler or macrovasculer complication. At present, there is little evidence for the correlation duration of diabetes mellitus with cognitive dysfunction.The aim of this study is to asses the correlation between duration and cognitive dysfunction This is a cross-sectional study.The subjects are the patient who came to the endokrin policlinic sardjito hospital in Yogyakarta with consecutive sampling. We used Montreal Cognitive Assement Indonesian version. Correlation between duration and cognitive dysfunction were tested with Spearmanâs test and linear regression modelfor multivariate analysis. The results were considered as statistically if the p value<0,05. A total 51 subjects were participated in this study. Cognitive dysfuncton was reported by 32 (62,7%) subjects with duration 12,13Â±SD7,79.(r=-0,424, p=0,002), it means that the longer duration the cognition worst. Analysis multivariate with regression linear demonstrated that negative correlation between duration and cognitive dysfunction (Î²=-0,363, p= 0,008) it means duration is the independent variabel with direct correlation with cognitive dysfunction. Conclusion of this study there was a correlation between duration and cognitive dysfunction with moderate strength.